2019
DOI: 10.1007/s10006-019-00806-w
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quality of life after surgery of head and neck cancer with microvascular reconstruction: a prospective study with 4.9-years follow-up

Abstract: Purpose The aim of this study was to evaluate the long-term health-related quality of life (HRQoL) of head and neck cancer patients with microvascular surgery. Surgical treatment causes great changes in patient HRQoL. Studies focusing on long-term HRQoL after microvascular reconstruction for head and neck cancer patients are scarce. Methods We conducted a prospective study of 93 patients with head and neck cancer and microvascular reconstruction in Helsinki University Hospital Finland. HRQoL was measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…There is a limited number of previous studies focusing on long-term QoL in head and neck cancer survivors operated with free flap reconstruction. The present results are in line with the results reported by relatively recent Finnish study with a narrower range of assessments [ 7 ]. The probable reason for limited number of studies is the high mortality in this patient group but also the small cohorts limiting the possibilities for long-term follow-up.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There is a limited number of previous studies focusing on long-term QoL in head and neck cancer survivors operated with free flap reconstruction. The present results are in line with the results reported by relatively recent Finnish study with a narrower range of assessments [ 7 ]. The probable reason for limited number of studies is the high mortality in this patient group but also the small cohorts limiting the possibilities for long-term follow-up.…”
Section: Discussionsupporting
confidence: 93%
“…According to our knowledge, most of the previous studies have reported the evaluations only up to 2 years after the operation and the number of studies focusing on the QoL in a longer follow-up is limited. In one Finnish survey, the QoL was assessed with 15D-tool and the study showed a reduction in the QoL during a 5-year follow-up [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sensory morbidities vary largely between 0% and 46% 9 and incidences of neuropathic pain in the donor-site have, to our knowledge, not been reported in the literature. As RFFF surgery is often performed as a part of oncological head and neck reconstructions, follow-up focuses on the survival of the disease or severely disabling complications in the recipient site, including speech and mastication impairment 10 , rather than on pain in the donorsite. Therefore, neuropathic pain in the donor -site is likely to be missed or underdiagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…It was published in 1981 according to the WHO definition of health and revised in 1986 and 1992. Because of the vast accumulated experience with its use during the last few decades, it has been used to assess various health conditions for common otolaryngologic diseases [ 11 , 12 , 13 , 14 ]. This allows for good comparability in this area of research.…”
Section: Introductionmentioning
confidence: 99%